A sensitive electrochemical immunosensor for the detection of squamous cell carcinoma antigen by using PtAu nanoparticles loaded on TiO2 colloidal spheres as labels. Issue 74 (13th August 2015) - Ma, Hongmin; Wang, Yaoguang; Zhang, Hui; Wu, Dan; Guo, Aiping; Yan, Tao; Wei, Qin; Du, Bin
<x xml:space="preserve">Abstract</x> A sensitive sandwich-type electrochemical immunosensor for detection of squamous cell carcinoma antigen (SCCA) was developed by using PtAu nanoparticles loaded on TiO2 colloidal spheres (PtAu/TiO2) as secondary-antibody (Ab2) labels.